A long-lasting wireless stimulator for small mammals - Hentall, Ian D. (Frontiers in Neuroengineering, 2013)
The chronic effects of electrical stimulation in unrestrained awake rodents are best studied with a wireless neural stimulator that can operate unsupervised for several weeks or more. A robust, inexpensive, easily built, cranially implantable stimulator was developed to explore the restorative effects of brainstem stimulation after neurotrauma. Its connectorless electrodes directly protrude from a cuboid epoxy capsule containing all circuitry and power sources. This physical arrangement prevents fluid leaks or wire breakage and also simplifies and speeds implantation. Constant-current pulses of high compliance (34 volts) are delivered from a step-up voltage regulator under microprocessor control. A slowly pulsed magnetic field controls activation state and stimulation parameters. Program status is signaled to a remote reader by interval-modulated infrared pulses. Capsule size is limited by the two batteries. Silver oxide batteries rated at 8 milliamp-hours were used routinely in 8 mm wide, 15 mm long and 4 mm high capsules. Devices of smaller contact area (5 by 12 mm) but taller (6 mm) were created for mice. Microstimulation of the rat’s raphe nuclei with intermittent 5-minute (50% duty cycle) trains of 30 µA, 1 ms pulses at 8 or 24 Hz frequency during 12 daylight hours lasted 21.1 days ±0.8 (mean ± standard error, Kaplan-Meir censored estimate, n=128). Extended lifetimes (>6 weeks, no failures, n=16) were achieved with larger batteries (44 milliamp-hours) in longer (18 mm), taller (6 mm) capsules. The circuit and electrode design are versatile; simple modifications allowed durable constant-voltage stimulation of the rat’s sciatic nerve through a cylindrical cathode from a subcutaneous pelvic capsule. Devices with these general features can address in small mammals many of the biological and technical questions arising neurosurgically with prolonged peripheral or deep brain stimulation.